Gall Nuts Cynips quercusfolii (Linnaeus) and Andricus infectorius (Hartig) as Tannin Raw Materials - Maciej Bilek; Zbigniew Czerniakowski; Katarzyna Kozłowska-Tylingo; Michał Gostkowski; Tomasz Olbrycht; Cuneyt Cicek; Paweł Staniszewski; Tomasz Dudek (Applied Sciences, 2022)
The study included gall nuts caused by Cynips quercusfolii collected from Quercus robur and Andricus infectorius, harvested from Quercus infectoria. The evaluation of the percentage content of tannins expressed as a pyrogallol was performed using the analytical methodology recommended by the current “European Pharmacopoeia 10”. In order to compare the chemical composition of the tested samples, chromatographic profiles and ion mass distribution spectra were made using high-performance liquid chromatography techniques coupled with two types of detection: spectrophotometry and mass spectrometry. The average content of tannins expressed as pyrogallol for C. quercusfolii ranged from 13.36% to 14.74%, while for A. infectorius it was from 34.77% to 39.95%. The comparison of both the mass spectra and the chromatographic profiles shows a high similarity of all samples of C. quercusfolii and large differences in the chemical composition compared to A. infectorius. The tested C. quercusfolii should be considered a much poorer tannin source than A. infectorius. It cannot be simultaneously treated as its substitute raw material due to the lower tannins percentage content and different chemical composition. However, compared to other Central European herbal raw materials, C. quercusfolii gall nuts are an alternative tannin source with potential use in herbal medicine and the pharmaceutical industry.